2014
DOI: 10.4103/1450-1147.138576
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Body Burden Measurements in 131 Iodine Therapy for Differentiated Thyroid Cancer: Effect of Recombinant Thyroid Stimulating Hormone in Whole Body 131 Iodine Clearance

Abstract: Protocols in the management of differentiated thyroid cancer, recommend adequate thyroid stimulating hormone (TSH) stimulation for radioactive 131I administrations, both for imaging and subsequent ablations. Commonly followed method is to achieve this by endogenous TSH stimulation by withdrawal of thyroxine. Numerous studies worldwide have reported comparable results with recombinant human thyroid stimulating hormone (rhTSH) intervention as conventional thyroxine hormone withdrawal. Radiation safety applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Absolute values for whole-body half-life differ in the literature. Ravichandran et al reported about 16.45 h in the hypothyroidism group versus 12.35 h in the rhTSH group (11,13). Our values for whole-body half-life were longer with 22.7 6 11.6 h for hypothyroid male and 18.1 6 5.1 h for hypothyroid female patients whereas in the rhTSH group values were 18.0 6 6.6 h for male and 15.9 6 3.7 h for female patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Absolute values for whole-body half-life differ in the literature. Ravichandran et al reported about 16.45 h in the hypothyroidism group versus 12.35 h in the rhTSH group (11,13). Our values for whole-body half-life were longer with 22.7 6 11.6 h for hypothyroid male and 18.1 6 5.1 h for hypothyroid female patients whereas in the rhTSH group values were 18.0 6 6.6 h for male and 15.9 6 3.7 h for female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Second, whole-body scintigraphy for response assessment is associated with low radiation exposure and currently in our clinic done almost exclusively with rhTSH. Table 7 compiles publications comparing the effect of hypothyroidism and rhTSH on whole-body dose, half-life, or residence time (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Most publications are based on studies with a limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations